Recent Advances in the Message Passing Interface 18th European MPI Users' Group Meeting, EuroMPI 2011, Santorini, Greece, September 18-21, 2011. Proceedings - Cotronis, Yiannis; Danalis, Anthony; Nikolopoulos, Dimitris; Dongarra, Jack (Programming and Software Engineering, 2011)
This book constitutes the refereed proceedings of the 18th European MPI Users' Group Meeting on Recent Advances in the Message Passing Interface, EuroMPI 2011, held in Santorini, Greece, in September 2011. The 28 revised full papers presented together with 10 posters were carefully reviewed and selected from 66 submissions. Topics covered are communication; I/O; networking, and implementation issues and improvements; algorithms and tools; interaction with hardware; applications and performance evaluation; fault and tolerance.